ANALISIS KESELAMATAN DAN KESEHATAN KERJA (K3) DI PELABUHAN PENYEBERANGAN FERRY BIRA - Ratih Purwasih (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
Ports are facilities at the end of oceans, rivers, and lakes for receiving ships and moving cargo or passengers within their depths. Ports usually have specially designed tools for loading and unloading ships that are anchored. The port is also a gateway to enter a certain area as a connecting infrastructure between regions, between islands and even between countries. The port is made based on public demand. One of the functions of the port is to facilitate access for Indonesian people to travel from one island to another. This research was conducted based on the technical condition of the Bira Ferry Crossing Port, which requires service devices and sea transportation passenger terminal facilities that are in accordance with their functions and can support the safety and security of passengers and workers. The government must make comprehensive improvements to the dock conditions at the Bira Ferry Crossing Port. Maintenance of public facilities and supporting ferry crossing docks needs to be improved, so that port activities take place safely.